Healthcare-Associated Infections in patients with Covid-19: Assessment of commorbidities and risk of mortality (Research, Society and Development, 2024)
Healthcare-associated infections are a known factor that is especially difficult to control within healthcare institutions. They are responsible for increased mortality, as well as increased length of stay and costs. This is a retrospective observational cross-sectional study that aims to elucidate information about infections acquired in the hospital environment by patients with a confirmed diagnosis of COVID-19, who are more susceptible to this condition; it was conducted from March 2020 to March 2022 at a hospital in the southern region of Brazil. Data were collected from electronic medical records, and the profile of these infections was defined; the frequencies of the main comorbidities and main infections were analyzed, with site and etiological agent being discriminated, and the antimicrobials that were used being specified. The mortality rate of patients with obesity was 2.3 times higher, while that of pregnant and postpartum women was 11.3 times higher.